Self-attributions and perceptions of socializers' attributions as predictors of self-concepts: different findings for girls and boys in math and German - Reschke, Katharina; Hertel, Silke; Spinath, Birgit (Learning and individual differences, 2024)
With this study, we aimed to expand the understanding of gender differences in students' self-concepts in math and German. To this end, we investigated the roles of students' self-attributions and their perceptions of parents' and teachers' attributions for success and failure in math and German in predicting students' self-concepts. Also, we controlled for students' achievement and included social and dimensional comparison effects (I/E model and DCT). In a cross-sectional design, a sample of N = 723 eighth graders (age M = 14.23, SD = 0.68) self-reported their self-concepts and grades in math and German. Moreover, students indicated their beliefs on how much they, their parents, and their teachers think that their abilities are responsible for their successes and failures in math and German. We found gender differences in students' self-concepts and ability attributions in favor of boys in math and girls in German. Furthermore, we found that, beyond grades, concurrent predictions of students' self-concepts from students' self- and perceived attributions depended on gender. Whereas ability attributions for success in math predicted only boys' self-concepts, ability attributions for failure in math predicted only girls' self-concepts. Moreover, dimensional comparison effects of achievement on self-concepts emerged only for math, but not for German (for both genders). Perceptions of parents' and teachers' attributions predicted students' self-concepts mainly via students' own attributions. Our findings demonstrate the potential importance of attributions for students' self-concepts. Implications for future educational and psychological research and practice are discussed.
Online verfügbar: 19. Juni 2024
Gesehen am 05.09.2025